Kajian Tanaman Inang Nematoda Puru Akar Padi (Meloidogyne graminicola) - Mulyadi Mulyadi; B. Triman (Jurnal Perlindungan Tanaman Indonesia, 1995)
The objective of the research was to study host plants or alternate hosts of root-knot nematode of rice (Meloidogyne graminicola). At the first phase research, ten rice cultivars were inoculated with M. graminicola. On the second phase, nineteen species of plants were treated with M. graminicola. Both experiments were done in green house in Completely Randomized Design. The third phase research was conducted as a survey method using “proportional random sampling”, with D.I. Yogyakarta as its survey areas.  The research results indicated that all rice cultivars tested were attacked by M. graminicola. The lowest number of root-gall was found in IR 26. Of the 19 species plants tested, soybean, pea common bean, france bean, cabbage, and sugarcane var. Ps 56 were attacked by M. graminicola. The survey results indicated that 15 species of weeds were invaded by M. graminicola, i.e. Coix lacrymajobi, Comelina nudiflora, Cyperus flavidus, C. iria, Echinochloa colona, Eragrotis amabilis, Fimbristylis pilosa, Ichaimum mutichum, Leersia hexandra, Ludwigia adscendens, L. peruviana, Marsilea crenata, Monochoria vaginalis, Polygonum barbatum, and Stagnima sp. The highest populatiom of M. graminicola was found on E. colona.